(untitled) (Global Journal of Management and Business Research, 2021)
Introduction-Customer is the center of any business in the present business world. The products are evolving every day to meet the changing customer demand, so as the company strategies. Brand image is playing a key role in the sales of the product. Brand evo-lotion is important to keep brands fresh, vital, and relevant to the contemporary market (Merrilee’s, 2005)). Brands are now being extended to sub-brands to lever-age the master brand image, thereby increasing the sales. Therefore, the sales strategies must be adapted according to the brands and sub brands to stay competitive in the market. There is very less literature on the topic of sales strategies, subbrands and how to design sales strategies for sub-brands.